A Transcranial Stimulation Intervention to Support Flow State Induction - Gold, Joshua; Ciorciari, Joseph (Frontiers in Human Neuroscience, 2019)
Background: Flow states are considered a positive, subjective experience during an optimal balance between skills and task demands. Previously, experimentally induced flow experiences have relied solely on adaptive tasks. Objective: To investigate whether cathodal transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex (DLPFC) area and anodal tDCS over the right parietal cortex area during video game play will promote an increased experience of flow states. Methods: Two studies had participants play Tetris or first-person shooter (FPS) video games while receiving either real tDCS or sham stimulation. Tetris recruited nineteen untrained players who infrequently played video games while the ten FPS participants played FPS frequently. Flow experience was assessed before and after stimulation. Results: Compared to sham stimulation, real stimulation increased flow experience for both untrained Tetris and trained FPS players. No ceiling effects were noticed between trained and untrained groups. Conclusion: Cathodal and anodal tDCS over the left DLPFC and right parietal areas respectively may encourage flow experiences in complex real-life motor tasks that occur during sports, games and everyday life.